Optimizing Land Allocation for Paddy Varieties Using Linear Programming: A Case Study of Pawaga, Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Farmers often operate with limited resources, making strategic and scientifically informed decision-making essential. Linear programming is one such analytical tool that can support optimal resource allocation. A case study was conducted in Pawaga, Iringa District, Tanzania, with the aim of evaluating the gross profit  of growing four paddy varieties namely Shingo ya mwali, Faya, Saro 5 and Zambia, using linear programming. Farmers in the area typically select crop varieties based on intuition or peer influence, which can lead to suboptimal profitability. A study was conducted to determine the gross revenue per acre for different paddy varieties, asses their variable production costs, and compute their gross profits. Linear programming was then applied using Microsoft Excel Solver to identify the best land allocation that would maximize overall farm profit.  A farmer should allocate the 4 acres of land by growing 2.7 acres of paddy Shingo ya mwali, and 1.3 acres of paddy Saro 5, so as to generate a gross profit of 7,680,400 shillings, under the operating cost of 4,167,000 shillings. The results show that the gross profit obtained through the LP model is superior to that obtained through the traditional method by 6%.This suggests that, by reallocating the same land and operating under the same budget constraints, farmers could increase their gross profit compared to their current practices. The study concludes that scientific tools such as linear programming can significantly improve crop planning and encourages farmers to transition from experience-based decision-making to data-driven strategies for enhanced profitability.